J'ai besoin d'aide !! SVP ! Merci d'avance !! :)
Développe puis réduis ces expressions :

A = (x - 2)(x+2) E = (5 + 4g)(5 - 4g)
B = (5- y )(5+y) F = ( 2.1x - 3)(2.1+ 3)
C = (3x + 5)(3x -5) G = (2i +6.1)(2i - 6.1)
D = (10-7z)(10+7z) H = ( 3.2j + 4)(4 - 3.2j)

2

Réponses

2013-10-28T09:58:56+01:00
A = (x - 2)(x+2)=x²-4

E = (5 + 4g)(5 - 4g)=25-16g²

B = (5- y )(5+y)=25-y²      
         
F = ( 2.1x - 3)(2.1+ 3)=4.41x²-9

C = (3x + 5)(3x -5)=9x²-25

G = (2i +6.1)(2i - 6.1)=4i²-37.21

D = (10-7z)(10+7z)=100-49z²

H = ( 3.2j + 4)(4 - 3.2j)=-10.24i²+16
2013-10-28T10:33:01+01:00
A = ( x - 2 ) ( x + 2 )
= x * x + x * 2 + (-2) * x + (-2) * 2
= x^2 + 2x - 2x - 4
= x^2 - 4

B = ( 5 - y ) ( 5 + y )
= 5 * 5 + 5 * y + (-y) * 5 + (-y) * y
= 25 + 5y - 5y - y^2
= 25 - y^2

C = ( 3x + 5 ) ( 3x - 5 )  
= 3x * 3x + 3x * (-5) + 5 * 3x + 5 * (-5)
= 9x^2 - 15x + 15x - 25
= 9x^2 - 25

D = ( 10 - 7z ) ( 10 + 7z ) 
= 10 * 10 + 10 * 7z + (-7z) * 10 + (-7z) * 7z
= 100 + 70z - 70z - 49z^2
= 100 - 49z^2

E = ( 5 + 4g ) ( 5 - 4g )
= 5 * 5 + 5 * (-4g) + 4g * 5 + 4g * (-4g)
= 25 - 20g + 20g - 16g^2
= 25 - 16g^2

F = ( 2,1x - 3 ) ( 2,1 + 3 )
= 2,1x * 2,1 + 2,1x * 3 + (-3) * 2,1 + (-3) * 3
= 4,41x + 6,3x - 6,1 - 9
= 10,71x - 15,1

G = ( 2i + 6,1 ) ( 2i - 6,1 )
= 2i  * 2i + 2i * (-6,1) + 6,1 * 2i + 6,1 * (-6,1)
= 2i^2 - 12,2i + 12,2i - 37,21
= 2i^2 - 37,21

H = ( 3.2j + 4 ) ( 4 - 3.2j )
= 3,2j * 4 + 3,2j * (-3,2j) + 4 * 4 + 4 * (-3,2j)
= 12,8j - 10,24j^2 + 16 - 12,8j
= -10,24j^2 + 16